If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(x + -4) = -32 Reorder the terms: -8(-4 + x) = -32 (-4 * -8 + x * -8) = -32 (32 + -8x) = -32 Solving 32 + -8x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -8x = -32 + -32 Combine like terms: 32 + -32 = 0 0 + -8x = -32 + -32 -8x = -32 + -32 Combine like terms: -32 + -32 = -64 -8x = -64 Divide each side by '-8'. x = 8 Simplifying x = 8
| 5x-11=8x+25 | | 31+25x=-10 | | 100=r-30 | | 3+4x-5x=14 | | 10w+20w+200=650 | | 8x+6y=330 | | 6-(3x-5)=7x-5 | | -8+4x+6x=62 | | 2(4r+6)=8(r+2) | | 14x+12y=690 | | -3+7x-3x=-47 | | 4x-4+98=18x-4 | | 25=q-13 | | -2x-8+4x=4 | | 15=x+6x+8 | | a-4=34 | | X+28=110 | | -5p-14= | | -4/9+(-2.8)= | | -6-4x=-50 | | -5p+-14= | | (s/2)+8=54 | | p-4.8=6 | | 5.9v-1.3=2.3v+1.3 | | 2(3a+9)-30=3(2a-4) | | -443=8(9a-9)+5a | | 6n-4=n+19 | | (5/6)x=35 | | x(4+9)= | | -22=p+13.78 | | (7/9)x=42 | | X^3+5x+6x=0 |